Reassessing the Grammar Translation Method: Evidence from teaching the simple past tense in Islamic higher education - Mil'ul Hana Muharror; Rosiana Rosiana; Ahdi Riyono; Diah Kurniati (Indonesian Journal of Education and Pedagogy, 2026)
This study examined the efficiency of the Grammar Translation Method (GTM) in improving the understanding of university students regarding the Simple Past Tense. It employed one-group pre-test and post-test experimental design with 24 first-semester students of the Department of Islamic Education, Faculty of Tarbiyah and Teaching Sciences, IAI Khozinatul Ulum Blora. The students completed a pre-test to determine their prior knowledge, followed by three teaching sessions involving each of the GTM components with explicit grammar explanation, translation practice, and sentence-pattern drills. Post-test was then employed to measure learning gain quantitatively. Data analysis involved Shapiro–Wilk normality test, descriptive statistics, and paired-sample t-test to assess the significance of variations in scores. Findings indicated that the pre-test mean score of 61.25 improved to 70.83 in the post-test, and the paired-sample t-test indicated a statistically significant difference (t = -8.536, df = 23, p = 0.000). Thus, the null hypothesis was rejected, supporting the fact that the Grammar Translation Method significantly improved students' command of the Simple Past Tense. These results suggest that GTM remains an effective and useful way to teach grammar, particularly for low-exposure students.